Eight-year (2007–2014) trends in ambient fine particulate matter (PM2.5) and its chemical components in the Capital Region of Alberta, Canada. (May 2016) - Bari, Md. Aynul; Kindzierski, Warren B.
Abstract: Currently there have been questions about ambient fine particulate matter (PM2.5 ) levels in the Capital Region of Alberta, Canada. An investigation of temporal trends in PM2.5 and its chemical components was undertaken in the City of Edmonton within the Capital Region over an 8-year period (2007–2014). A non-parametric trend detection method was adopted to characterize trends in ambient concentrations. No statistically significant change was observed for ambient PM2.5 concentrations during 2007–2014, while significant decreasing trends were found for organic carbon, elemental carbon, oxalate, barium, lead and cadmium. A statistically significant increasing trend was observed for sodium chloride indicating an increase of de-icing salt contribution for winter road maintenance in recent years. Concentrations of potassium ion and zinc exhibited strong and significant seasonal variability with higher concentrations in winter than in summer likely reflecting wood smoke origins more than other potential sources in Edmonton and the surrounding region. No statistically significant changes were observed for all other chemical components examined. Notwithstanding robust population growth that has occurred in Edmonton, these findings reveal that particulate air quality and corresponding trace elements in Edmonton's air has been unchanged or improved over the investigated period (2007–2014). Longer-term air quality monitoring at least over several decades is needed to establish whether trends reported here are actually occurring. Highlights: No change observed for PM2.5 at Alberta Capital Region over an 8-year period Downward trends observed for ambient levels of OC, EC, oxalate, Ba, Pb and Cd Increasing trend observed for NaCl indicating road salt contribution in winter High winter levels of K + and Zn reflect wood smoke origins more than other sources.